PENGEMBANGAN ADMINISTRASI KEUANGAN BERBASIS FOXPRO UNTUK MENINGKATKAN EFEKTIFITAS PROGRAM KERJA DI MTS - Hamida, Ida; Kusumaningsih, Widya; Ginting, Rosalina Br (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The implementation of the FoxPro-based madrasah financial administration system, especially in the payment of infaq/SPP and reporting of budget use, which aims to improve the efficiency of the madrasah work program, faces various obstacles. Initial observations show that the management of financial administration is still done manually, so it is less effective and efficient, less transparent and not well documented. In addition, limited time and resources cause the infaq/SPP payment process to not be carried out optimally. As a result, the madrasah program was not implemented in accordance with the RKAM that had been planned in the budget year. The method in this study is Research and Development, with the ADDIE model. Data collection techniques by interview, questionnaire and observation. Data validity testing uses data source triangulation. The development stage involves experts and practitioners. The validity stage is carried out with a validation questionnaire from media experts and material experts, field trials, and effectiveness analysis to determine the effectiveness of the development of the FoxPro-based madrasah financial administration system. The results of the study on the Analysis of the Effectiveness of the Development of a FoxPro-based Madrasah Financial Administration System can be seen in a field trial involving 30 students at MTs Wahid Hasyim Warungasem, a total score of 2,135 was obtained with a maximum score of 2,400, so that an effectiveness value of 89% was obtained with a valid category. This shows that the development of a FoxPro-based Madrasah Financial Administration System is effective and feasible to be implemented at MTs Wahid Hasyim Warungasem. ABSTRAKPelaksanaan sistem administrasi keuangan madrasah berbasis FoxPro terutama dalam pembayaran infaq/SPP dan pelaporan penggunaan anggaran, yang bertujuan untuk meningkatkan efesiensi program kerja madrasah menghadapi berbagai kendala. Observasi awal menunjukkan bahwa pengelolaan administrasi keuangan masih dilakukan secara manual, sehingga kurang efektif dan efesien, kurang transparan serta tidak terdokumentasi dengan baik. Selain itu, keterbatasan waktu dan sumber daya menyebabkan proses pembayaran infaq/SPP tidak dapat dilakukan secara optimal. Akibatnya, program madrasah tidak terlaksana sesuai dengan RKAM yang sudah terancana pada tahun anggaran. Metode dalam penelitian ini adalah Research and Development, dengan model ADDIE. Teknik pengumpulan data dengan cara wawancara, angket dan observasi. Uji keabsahan data menggunakan triangulasi sumber data. Tahap pengembangan melibatkan ahli dan praktisi. Tahap validitas dilakukan dengan angket validasi ahli media dan ahli materi, ujicoba lapangan, serta analisis efektifitas untuk mengetahui efektifitas pengembangan system administrasi keuangan madrasah berbasis FoxPro. Hasil penelitian pada Analisis Efektifitas Pengembangan system administrasi keuangan madrasah berbasis FoxPro ini, dapat terlihat pada ujicoba lapangan yang melibatkan 30 siswa di MTs Wahid Hasyim Warungasem diperoleh jumlah skor 2.135 dengan skor maksimal 2.400 sehingga diperoleh nilai efektifitas sebesar 89% dengan kategori valid. Hal ini menunjukkan bahwa pengembangan system administrasi keuangan madrasah berbasis FoxPro ini efektif dan layak diterapkan di MTs Wahid Hasyim Warungasem.